Plain radiographic indices are reliable indicators for quantitative bone mineral density in male and female patients before total hip arthroplasty - Sebastian Rohe; Sabrina Böhle; Georg Matziolis; Benjamin Jacob; Steffen Brodt (Scientific Reports, 2023)
Abstract Osteoporosis is underdiagnosed in patients undergoing total hip arthroplasty (THA). Bone mineral density measurement by dual-energy X-ray absorptiometry (DXA) is the gold standard, but indices on plain hip radiographs also seemed to be reliable screening tools in female or Asian ethnicities in previous studies. Given the lack of knowledge about male patients and Caucasian ethnicities, this study was conducted to evaluate plane hip radiographic indices as a screening tool for osteopenia and osteoporosis in Caucasian female and also male patients before undergoing THA. A retrospective analysis of 216 elderly patients with pre-existing DXA before hip arthroplasty was performed and four indices were calculated on plain hip radiographs: Canal-Flare-Index (CFI), Canal-Calcar-Ratio (CCR), Canal-Bone-Ratio (CBR) 7 and 10 cm below the lesser trochanter. They were correlated with femoral neck DXA T-scores by Pearson’s correlation and intraclass correlation coefficient, and a ROC analysis was performed. A total of 216 patients (49.5% male) were included. CBR-7 and -10 were highly correlated (p < 0.001) with femoral neck T-score in males (Pearson’s correlation CBR-7 r = − 0.60, CBR-10 r = − 0.55) and females (r = − 0.74, r = − 0.77). CBR-7 and -10 also showed good diagnostic accuracy for osteoporosis in the ROC analysis in males (CBR-7: AUC = 0.75, threshold = 0.51; CBR-10: 0.63; 0.50) and females (CBR-7: AUC = 0.87, threshold = 0.55; CBR-10: 0.90; 0.54). Indices such as the Canal Bone Ratio (CBR) 7 or 10 cm below the lesser trochanter on plain hip radiographs are a good screening tool for osteopenia and osteoporosis on plain hip radiographs and can be used to initiate further diagnostics like the gold standard DXA. They differ between male and female patients.